A Study on Women Empowerment and Entrepreneurial Intention among Small Business of Women Entrepreneurs in the Czech Republic - J. Jose Prabhu (Quantitative Economics and Management Studies, 2020)
Entrepreneurship refers to establishing of a brand-new business to take advantages from brand-new chances. Entrepreneur is the vital element of entrepreneurship and also now women in Czech Republic are additionally effective in this as they have qualities preferable for entrepreneurship advancement. Entrepreneurship is a much ideal profession for women than regular work. Females are thought about an important human resource of the country and every state need to try to utilize them as arbitrators of economic growth and also advancement. Empowerment of women has actually become a vital concern in current times. This write-up manages empowerment of country females via entrepreneurship as well as the benefits entrepreneurship among the small company. "Economic empowerment of females resulted in development of household as well as Neighborhood". This principle purpose of the research study is to identify the economic empowerment of women business owners. The example size of the study is 100 respondents. The data collected went through online form structured questionnaire as well as the devices utilized for analysis percentage analysis and also ANOVA test. This declaration is confirmed by a cumulative small business entrepreneurship in the Czech Republic.